Speech auditory brainstem response in audiological practice: a systematic review - BAŞÖZ, MELIHA; Başöz Behmen M.; KURU, ELIF; Güner N.; GEDİK, ÖZGE; Kuru E.; Bal N.; Gedik Toker Ö. (My University, 2023)
Background: Speech-ABR is an auditory brainstem response that evaluates the integrity of the temporal and spectral coding of speech in the upper levels of the brainstem. It reflects the acoustic properties of the stimulus used and consists of seven major waves. Waves V and A represent the onset of the response; wave C transition region; D, E, and F waves periodic region (frequency following response); and wave O reflects the offset of the response.PurposeThe aim of this study is to evaluate the clinical availability of the speech-ABR procedure through a literature review.MethodsLiterature search was conducted in Pubmed, Google Scholar, Scopus and Science Direct databases. Clinical studies of the last 15 years have been included in this review and 60 articles have been reviewed.ResultsAs a result of the articles reviewed, it was seen that most of the studies on speech ABR were conducted with children and young people and generally focused on latency analysis measurements. Most used stimulus is the /da/ syllable.ConclusionsSpeech ABR can objectively measure the auditory cues important for speech recognition and has many clini- cal applications. It can be used as a biomarker for auditory processing disorders, learning disorders, dyslexia, otitis media, hearing loss, language disorders and phonological disorders. S-ABR is an effective procedure that can be used in speech and language evaluations in people with hearing aids or cochlear implant. It may also be of benefit to the aging auditory system\"s ability to encode temporal cues.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)